2006
DOI: 10.1111/j.1083-6101.2006.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Email Copies in Workplace Interaction

Abstract: This study examines how employees in a distributed work group use email copies in networks of collaboration. It studies the audience design of messages with multiple recipients, analyzing explicit and implicit addressing devices used to appoint recipients as primary and secondary participants in the interaction. Copying in recipients serves to share knowledge of ongoing projects and to build up a common information pool. Furthermore, it is used to facilitate multi-party interaction and to build personal identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 28 publications
(37 reference statements)
1
47
0
Order By: Relevance
“…Furthermore, we see how such practices emulate those of prior arrangements such as email where the "copying in" of recipients, as a form of tagging, invited participation beyond the primary addressee (Skovholt and Svennevig 2006). Indeed, this practice of copying pre-dates email, as Skovholt and Svennevig elaborate, the copying of letters preceded this.…”
Section: Editorial Ethicsmentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, we see how such practices emulate those of prior arrangements such as email where the "copying in" of recipients, as a form of tagging, invited participation beyond the primary addressee (Skovholt and Svennevig 2006). Indeed, this practice of copying pre-dates email, as Skovholt and Svennevig elaborate, the copying of letters preceded this.…”
Section: Editorial Ethicsmentioning
confidence: 73%
“…In the case of his cousin, Jason had connected with her as an adult and was not expecting her to give her children access to his profile -he only had adult friends. In contrast to studies of email then, which posit the regulatory potential, and specifically compliance, brought about by copying in (Skovholt and Svennevig 2006), here the copying in of Jason's cousin (and her daughter), led to a destabilisation of the regulated environment his cousin was trying to construct and she did not "comply". Instead, she engaged in disconnective practice in an attempt to maintain her regulated environment.…”
Section: Public Ethicsmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, Markus [24] has found that people would put even simple requests in email just for the sole purpose of documentation. Further, email copies to third parties (team leader or project manager in this case) help to put pressure on the email addressee to conform to certain action required by the respondent [38] which is important during situations with high perceived RA. For instance, an example of an interview response indicating the importance of email to manage perceived risk of RA is: "I send email to primary guy and backup guy off-shore just in case primary guy doesn't respond or is not around.…”
Section: Discussionmentioning
confidence: 99%
“…When knowledge about the communication partner is limited, there is evidence that stereotypical conceptions are evoked about the group that the other party represents (Brigham and Corbett 1997;Romm and Pliskin 1997;Weisenband et al 1995; see also Waldvogel 2001 for an overview). Certain features of the medium such as distribution lists may also contribute to the reinforcement of existing structures (Brigham and Corbett 1997;Skovholt and Svennevig 2006).…”
Section: Research On Email In Organizations and Workplacesmentioning
confidence: 99%